1997
DOI: 10.1088/0031-9155/42/7/004
|View full text |Cite
|
Sign up to set email alerts
|

External audit of photon beams by mailed film dosimetry: feasibility study

Abstract: A feasibility study for mailed film dosimetry has been performed. The global reproducibility of the method is better than 2%. It is shown that the normalized sensitometric curve does not depend on photon beam quality in the range from Co-60 gamma-rays to 18 MV x-rays, although the dose per optical density decreases when the energy increases. The fading of the latent image before film processing is only 3% per month and the normalized sensitometric curve is not modified after a period of 51 days between irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…1͑a͒ and Table II show that there is a large variation in sensitometric curves between the Kodak films indicated by TAA, PAA, and AAA, which must be ascribed to differences in composition of the various batches of film originating from the three institutions. These differences are markedly larger than the values mentioned by some groups, 8,21 but in agreement with the strong dependence of shape of sensitivity curves on the production batch, as reported by others. 12,22 This difference in observation with II.…”
Section: A Batch Compositionsupporting
confidence: 91%
See 3 more Smart Citations
“…1͑a͒ and Table II show that there is a large variation in sensitometric curves between the Kodak films indicated by TAA, PAA, and AAA, which must be ascribed to differences in composition of the various batches of film originating from the three institutions. These differences are markedly larger than the values mentioned by some groups, 8,21 but in agreement with the strong dependence of shape of sensitivity curves on the production batch, as reported by others. 12,22 This difference in observation with II.…”
Section: A Batch Compositionsupporting
confidence: 91%
“…This somewhat smaller intra-versus interinstitutional batch variability might be fortuitous and due to the time and amount of film batches bought by a specific institution. The differences are, however, larger than the 1.6% ͑one standard deviation͒ mentioned by Novotny et al 21 The sensitometric curves of the CEA films were obtained from two batches, as indicated in Fig. 5, and demonstrate a large variation for both batches each over a period of about a year.…”
Section: Long-term Variation Of Sensitometric Curvesmentioning
confidence: 59%
See 2 more Smart Citations
“…Novotny et al 15 have shown that a decrease in optical density of about 3% ͑for a dose of 0.45 Gy͒ and 1.8% ͑for a dose of 1.5 Gy͒ was observed per month of delay between film irradiation and film processing. It was therefore assumed that the errors in our procedure induced by time fading were less than 1%.…”
Section: E Processing Conditions and Measuring Instrumentsmentioning
confidence: 99%